Predicting whistleblowing intentions among Ar-Rahnu institutions' employees in Malaysia: theory of planned behaviour perspectives / Wan Azmeer Wan Mahmood ... [et al.] - Wan Mahmood, Wan Azmeer; Mat Jusoh, Yusri Huzaimi; Wan Mohamad Noor, Wan Nurul Basirah; Abd Razak, Siti Noor Azmawaty; Wan Mustafa, Wan Muzlaina (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
Past research has indicated that whistleblowing serves as an effective tool to uncover violations in ethical practices. Nevertheless, few have studied whistleblowing in the context of Islamic pawn-broking scheme (Ar-Rahnu) despite the reported cases of unethical conducts perpetrated by its employees. Utilizing the Theory of Planned Behaviour, this study aims to identify the relationships among attitude, subjective norms and perceived behavioural control with the whistleblowing intention of employees in Ar-Rahnu institutions in Malaysia. The questionnaires were distributed to 250 employees of Ar-Rahnu institutions across the country. The data was analysed using Partial Least Squares Structural Equation Modelling Version 3.3.3 (PLS-SEM V 3.3.3). The results revealed that subjective norms and perceived behavioural control do have significant positive relationships with whistleblowing intention. Meanwhile, the employee's attitude was found to have an insignificant effect on whistleblowing intention. Theoretically, the study's outcome may contribute to the existing body of literature in the areas of whistleblowing. The findings might shed some practical insights into designing a more effective internal control mechanism by the management of Ar-Rahnu and policymakers in Malaysia so that the good governance practices shall be uplifted throughout the entire system